2012
DOI: 10.1021/la302765t
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Texturing on Superoleophobicity, Contact Angle Hysteresis, and “Robustness”

Abstract: Previously, we reported the creation of a fluorosilane (FOTS) modified pillar array silicon surface comprising ~3-μm-diameter pillars (6 μm pitch with ~7 μm height) that is both superhydrophobic and superoleophobic, with water and hexadecane contact angles exceeding 150° and sliding angles at ~10° owing to the surface fluorination and the re-entrant structure in the side wall of the pillar. In this work, the effects of surface texturing (pillar size, spacing, and height) on wettability, contact angle hysteresi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
124
2
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(132 citation statements)
references
References 20 publications
5
124
2
1
Order By: Relevance
“…66,67 When combined with the inherent high switching parameter, oil-water separation exceeding >98% efficiency is attained, Table 3. This performance matches existing oleophobic-hydrophilic systems for oil-water separation (which however tend to be far more complex in nature and fabrication methods).…”
Section: Discussionmentioning
confidence: 99%
“…66,67 When combined with the inherent high switching parameter, oil-water separation exceeding >98% efficiency is attained, Table 3. This performance matches existing oleophobic-hydrophilic systems for oil-water separation (which however tend to be far more complex in nature and fabrication methods).…”
Section: Discussionmentioning
confidence: 99%
“…The surfaces were reported to be reasonably stable under continuous drop impact, sand abrasion and annealing up to 400°C, but they showed damage under peel tests. Zhao et al 64 have discussed the theoretical considerations to assess the mechanical robustness of superoleophobic surfaces with arrays of micropillars. They indicated that smaller aspect ratio micropillars with a larger diameter provide better mechanical robustness.…”
Section: Surface Innovations Volume 1 Issue Si2mentioning
confidence: 99%
“…Specifically, curiosity on the meaning of apparent contact angles, such as advancing and receding contact angles, and contact angle hysteresis drives scientific debate and research in this area. [28][29][30][31][32][33][34] Progress is also driven by the fact that it became possible in recent years to measure the adhesion between a liquid droplet and a solid surface directly using a microbalance or other force-measuring systems. For example, Liu et al 35 studied the interaction between a liquid droplet and a series of gold substrates with wettability gradient by using a microbalance, and they found that the adhesion force decreases as the contact angle increases.…”
Section: Introductionmentioning
confidence: 99%